The Impact of Career Guidance Service Quality at the German Agency for International Cooperation on Service Recipients’ Satisfaction: The Role of Career Counselors as Mediating Factors, in Jordan - Harazneh, Amer Abdelqader (European Scientific Journal, ESJ, 2024)
The study aims to comprehensively understand and analyze service recipients’ overall satisfaction with their career counseling experience at the German Agency for International Cooperation in Jordan. The evaluation of this service varied significantly based on the diverse socio-demographic information collected from participants. Furthermore, the perceived quality of the career guidance service emerged as the most significant factor directly influencing the overall satisfaction levels of service recipients. study is based on quantitative approaches of the data collection process, a mixture of research methods. The structural model underwent analysis in two phases. In the initial stage (direct effect), the effect (QOS → ECC) was significant; thus, H1 was supported. The observed effects were significant in the range of ECC to STA, thereby supporting hypothesis 2. Since the results for QOS to STA were not significant, hypothesis 3 did not receive support. This study is the first to examine the role of career counselors at the GJU-CoB-CDC as mediating factors, influencing the relationship between the quality of career guidance services and the satisfaction of service recipients at GJU-CoB-CDC.